A low-cost system to control prehension force of a custom-made myoelectric hand prosthesis - Prakash, A.; Sharma, S. (Springer, 2020)
Purpose: In order to achieve stable and dexterous grasping of objects, prehension force control is quite a significant parameter for prosthetic hands. Commercially available hands such as bebionic, i-limb quantum and Michelangelo offer the precise grasping capability to perform activities of daily living (ADLs). However, the cost of such hands is too expensive for amputees residing in low-income countries. Methods: This paper introduces a low-cost, simple and efficient system for controlling the prehension force of a self-designed myoelectric prosthetic hand. A hand prototype was developed employing 3D printing technology and an intrinsic actuation approach. The hand fingers were equipped with a pre-calibrated force sensor for the online estimation of the grasp force. A closed-loop proportional-derivative (PD) based position control system was designed considering actuator as plant, electromyography (EMG) as a reference and grasp force as a feedback signal. Results: The results showed highly improved parameters, i.e. overshoot, offset and settling time of the proposed system than a simple open-loop system. These parameters guarantee faster closing of hand fingers and the production of accurate prehension force during finger-object interaction. Conclusion: Further, the myoelectric hand with a developed control scheme was successfully tested on five different transradial amputees for performing precise and faster grasping of different shaped objects. © 2020, Sociedade Brasileira de Engenharia Biomedica.
Keywords: Electromyography; Myoelectric prosthesis; Prehension force; Force sensor; Position control